Critical and analytical thinking skill in ecology learning: A correlational study - M. Mayarni; Eva Nopiyanti (University of Muhammadiyah Malang, 2021)
Critical and analytical thinking skills are included in higher-order thinking skills which become the focus of educational goals in recent era. This study aimed to determine the relationship between critical and analytical thinking skills in ecology learning at senior high school in East Jakarta. This research was conducted from March to June 2020. The research method used was descriptive correlational with associative research. This study involved 180 students. As many as 52 students were selected as research participants using cluster random sampling. The data were collected using a critical and analysis thinking rubric which was integrated to essay questions. The data analysis technique used was simple linear regression. The results indicates that there is significant correlation between students’ critical and analytical thinking skill (r = 0.812, r2 = 0.659, N = 52). In addition, students’ analytical thinking skill could be predicted using the regression equation y = 5.41 + 0.91x which means that it gives a positive effect to students’ critical thinking skills. The contribution of critical thinking skills with analytical thinking skills was 65.9%.